2018
DOI: 10.1093/cvr/cvy062
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy to decrease cardiac injury in aged heart following ischaemia-reperfusion: enhancement of the interaction between AMPK and SIRT1

Abstract: This editorial refers to 'Cardiomyocyte-specific deletion of Sirt1 gene sensitizes myocardium to ischaemia and reperfusion injury' by L. Wang et al., Myocardial injury is increased in aged hearts during ischaemia-reperfusion (IR) and accelerates the transition to post-infarct heart failure. 1Although many therapeutic interventions can effectively decrease cardiac injury in younger adult hearts, strategies to decrease cardiac injury in aged hearts are still limited.1 Therefore, understanding the mechanisms of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Accumulating evidence suggests that the activation of AMPK signaling pathway can significantly reduce myocardial injury in aging hearts. Li et al found that AMPK activation is markedly impaired in aged hearts following IR compared to young hearts [65]. They further found that cardiac SIRT1 mediates AMPK activation via LKB1(Liver kinase B1, LKB1) deacetylation, and AMPK modulates SIRT1 activity via regulation of NAD + level during MI.…”
Section: Ampk and Cardiac Agingmentioning
confidence: 98%
See 2 more Smart Citations
“…Accumulating evidence suggests that the activation of AMPK signaling pathway can significantly reduce myocardial injury in aging hearts. Li et al found that AMPK activation is markedly impaired in aged hearts following IR compared to young hearts [65]. They further found that cardiac SIRT1 mediates AMPK activation via LKB1(Liver kinase B1, LKB1) deacetylation, and AMPK modulates SIRT1 activity via regulation of NAD + level during MI.…”
Section: Ampk and Cardiac Agingmentioning
confidence: 98%
“…Importantly, the SIRT1 protein level and activity decline in aging heart, resulting in the impairment of the AMPK signaling. This suggests that SIRT1 and AMPK agonists have therapeutic potential for treatment of aging-related ischemic heart disease [65]. It has been shown that autophagy plays an active role in MI.…”
Section: Ampk and Cardiac Agingmentioning
confidence: 98%
See 1 more Smart Citation
“…Activation of the AMPK signaling pathway can significantly reduce myocardial injury in the elderly heart. AMPK can delay aging [32,33]. Exercise can activate the expression of AMPK in skeletal muscle and induce energy imbalance in muscles, leading to increased intracellular AMP and ADP concentrations.…”
Section: Discussionmentioning
confidence: 99%